Optimalisasi Penerapan Prinsip Good Governance Bidang Akademik dalam Upaya Mewujudkan Good University Governance - Hery Harjono Muljo; Aries Wicaksono; Ignatius Edward Riantono (Bina Nusantara University, 2014)
This study wants to know and understand whether good governance principles have been well applied as well as the factors influencing optimization of the implementation of good governance principles on the academic field in an effort to realize good university governance in Bina Nusantara University. The study aims to evaluate the implementation of good governance principles on the academic field, know the factors that affect the implementation of good governance principles on the academic field, and improve and develop the academic areas in accordance with good governance principles in order to maximize the role of Bina Nusantara University as Good University Governance. The approach model used to understand the implementation of good governance principles was a model to educational institution using the 8 principles, namely academic freedom, shared governance, clear rights and responsibilities, selection at merit, financial stability, accountability, regular testing of standards, and the importance of close cooperation. Research used qualitative method with descriptive analysis, by analyzing the factors influencing optimization of the implementation of good governance principles, particularly on academic areas. The results achieved there were 18 factors that affect the optimization of the implementation of good governance principles. Then the factors affected the optimization ofthe implementation of good governance principles the most are operational centralization and academic decentralization which were the novelty of this study.